A new species of the sandperch genus Parapercis from the western Indian Ocean (Perciformes: Pinguipedidae) - Ho, Hsuan-Ching; Heemstra, Phillip C.; Imamura, Hisashi (Zootaxa, 2014)
Parapercis albiventer sp. nov., a new species of sandperch is described based on 12 specimens collected from the western Indian Ocean. It can be distinguished from congeners by having a bright white ventral surface, without color markings on lower fourth of body; dorsal surface of head and body densely covered by small brown spots; a row of 10 faint reddish blotches on a paler background, along body axis; row of 10 deep reddish blotches, the lower part of each blotch with a solid black bar ventrally, below mid-lateral body axis; and combination of following characters: no palatine teeth; snout long; eye small; interorbital space broad; dorsal-fin rays V, 21; anal-fin rays I, 17; pectoral-fin rays 16–17; pored lateral-line scales 55–59; predorsal scales 9 or 10; scales on transverse row 6/17–21; 3 pairs of canine teeth at front of lower jaw; and vertebrae 10 + 20 = 30.